ANALISIS KALIBRASI CENTRIFUGES MENGGUNAKAN METODE ECRI 456-0595 - Zainal Abidin Siregar; Yulizham Yulizham (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2018)
Health equipment is a supporting tool for medical services. Health services tha are well sipported by equipment that is good, safe, and in accordance with its function so that there is no error in the patient's diagnosis. Calibration is aseries of actovities that form a relationship between the value indicated bt a measuring instrument system, or a values represented by a measuring material, with known value that are related to the magnitude measured in certain conditon.